Restoration of corticosteroid sensitivity by p38 Mitogen activated protein kinase inhibition in peripheral blood mononuclear cells from severe asthma - Mercado,N; Hakim,A; Kobayashi,Y; Meah,S; Usmani,OS; Chung,KF; Barnes,PJ; Ito,K (PLoS One, 2012)
BackgroundSevere asthma accounts for a small number of asthmatics but represents a disproportionate cost to health care systems. The underlying mechanism in severe asthma remains unknown but several mechanisms are likely to be involved because of a very heterogeneous profile. We investigated the effects of a p38MAPK inhibitor in corticosteroid sensitivity in peripheral blood mononuclear cells (PBMCs) from severe asthmatics and the profile of its responders.Methodology/Principal FindingsCorticosteroid sensitivity was determined by measuring dexamethasone inhibition of CD3/28 and TNF-α induced IL-8 production in PBMCs by using ELISA. PBMCs from severe asthmatics were relatively less sensitive to dexamethasone (Dex) as compared to those of non-severe asthmatics and healthy volunteers. The IC50 values of Dex negatively correlated with decreased glucocorticoid receptor (GR) nuclear translocation assessed using immunocytochemistry (r=−0.65; p<0.0005) and with decreased FEV1 (% predicted) (r=0.6; p<0.0005). A p38α/β inhibitor (SB203580) restored Dex-sensitivity in a subpopulation of severe asthma that was characterized by a defective GR nuclear translocation, clinically by lower FEV1 and higher use of oral prednisolone. We also found that SB203580 partially inhibited GR phosphorylation at serine 226, resulting in increased GR nuclear translocation in IL-2/IL-4 treated corticosteroid insensitive U937s.Conclusions/Significancep38MAPKα/β is involved in defective GR nuclear translocation due to phosphorylation at Ser226 and this will be a useful biomarker to identify responders to p38MAPKα/β inhibitor in the future.